Public Knowledge, Attitudes, and Practice towards COVID-19 Pandemic in Saudi Arabia: A Web-Based Cross-Sectional Survey - Alnasser, Ali Hassan A. (Med Sci (Basel), 2021)
(1) Background: COVID-19 has become a worldwide public health problem. No previous study has investigated factors associated with COVID-19 knowledge, attitude, and practice (KAP) after completely lifting the curfew in all Saudi Arabia regions and cities. Therefore, adequate knowledge, a positive attitude, and correct control of COVID-19 are essential to eradicate the disease. Hence, this study aims to assess factors associated with KAP of COVID-19; (2) Methods: This cross-sectional web-based survey was performed with the participation of 4305 individuals aged over 15 years living in Saudi Arabia from 11 to 19 August 2020. They were included using the snowball sampling method; (3) Results: Of the 4305 participants, 94.9% were Saudis, 60% females, and 45.4% were in the age group of 20–34 years, 61.7% married, and 49.3% from the Eastern Province of Saudi Arabia. Most of the participants demonstrated good KAP levels (89.6%, 87.2%, and 87.2%) towards the COVID-19 pandemic, respectively. In addition, most of the participants (85.8%) used the internet and social media as a source for COVID-19 information (4) Conclusions: The finding showed that most of the participants demonstrated good knowledge of COVID-19, positive attitudes, and demonstrated good practices for preventing the spread of disease infection.